Fabrication and Characterization of SiC Preforms for Metal Matrix Composites - Kisasoz, Alptekin; Guler, Kerem Altug; Karaaslan, Ahmet (CARL HANSER VERLAG, 2011)
In this study, the effect of the PVA amount on the SiC preform properties was investigated. SIC particulates that have 60 mu m average grain size were used as preform constituent. In order to produce SiC preforms, slurries that contains SIC, PVA, and colloidal silica were prepared with different amount of PVA and were dried at room temperature for 24 hours. Dried specimens were sintered at 1000 degrees C for 3 hours. Also, specimens were characterized by Archimedes' tests for porosity. Mechanical and microstructural tests were carried out by bending and SEM analysis, respectively.
Keywords: INFILTRATION; Materials Science